THE AUTHORITY OF MEDICAL ORGANIZATIONS IN DETERMINING THE OCCURRENCE OF MEDICAL MALPRACTICE - Panangngari, Andi Aulia; Muin, Audyna Mayasari; Mirzana, Hijrah Adhyanti (Al-Risalah, 2023)
This study aimed to examine and analyze the authority of medical organizations in determining the occurrence of medical malpractice and to examine and analyze the judge's consideration of Decision Number 1441/Pid/Sus/2019/PN Mks. This study used a normative juridical research method with a statute approach and a case approach. The data analysis employed descriptive qualitative analysis, which was correlated with concepts and theories from various literary sources. The results of the study revealed that the Indonesian Medical Association (IMA), through Honorary Council for Medical Ethics (HCME), was authorized to determine the occurrence of medical malpractice. This authority was manifested through the revocation of the license of the doctor who became the defendant, even though the judge's decision stated that no malpractice was found by the defendant. Regarding Decision Number 1441/Pid.Sus/2019/PN. Mks, the acquittal for Mrs. Dr. Elizabeth Susana M. Boing was right. Many opinions confirmed that the incident was a result of medical risks rather than medical malpractice committed by Mrs. Dr. Elizabeth. However, it was considered a work accident that resulted in a medical risk, which basically did not result in criminal sanctions.